In Vitro Determination of Wheat Dry Matter Solubility and Protein Digestibility - Rodica Căpriţă; Adrian Căpriţă; Iuliana Creţescu; Valeria Nicu (Scientific Papers Animal Science and Biotechnologies, 2023)
The objectives of the present study were to determine the in vitro dry matter (DM) solubility and protein digestibility (PD) of wheat grains. Two experiments were conducted. In experiment 1, samples were incubated for different time periods with pepsin, simulating gastric digestion, and in experiment 2, samples were digested following an in vitro two-step procedure, simulating gastric and small intestine digestion. DM solubility in gastric digestion showed an increase with the incubation time. DM solubility of wheat ranged in experiment 1 from 0.1532 g/g at 30 minutes digestion time, to 0.1714 g/g at 120 minutes digestion time. Samples showed higher DM solubility and PD after small intestine incubation than after gastric incubation. DM solubility increased with 16.67% and PD increased with 24.87% when gastric digestion was followed by 240 minutes intestinal digestion.